Nigeria’s Freedom of Information Act 2011, its Usage among Journalists in Katsina State - Ibrahim Abdulkadir (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
The aim of this study is to review the provisions of the freedom of information Act 2011, and investigate its usage among journalists in Katsina state. The study strives to find out whether journalists in Katsina state are aware of the Act, to assess provisions of the Act that give access to public information and find out whether journalists in Katsina state use the Act. In order to achieve these, the study used quantitative method whereby a survey was carried out using questionnaire as its tool of data gathering. The study was guided by the Social Responsibility theory as its theoretical framework. Findings indicate that the freedom of information Act contains more sections which deny access to public information than those that give access, and that journalists in Katsina State are aware of the Act. The study argues that ignorance on the part of some journalists and bureaucracy on the part of managers of public information are factors affecting the workability of the Act in Katsina State. The study recommends that all sections of the Act which deny access to information should be amended, stakeholders, governments at all levels, media owners and managers should organise workshops and seminars for journalists and the general public to enlighten them on the provisions of the Act and on how to use the Act. The media at all times should be allowed to publish or broadcast what it professionally deems fit for public consumption, without prior censorship. The Nigeria union of journalists and other media unions should make it mandatory that all registered journalists must buy a copy of the freedom of information Act. The study hopes to serve as a reference to all journalists in Katsina State in offering useful tips on the provisions and effective usage of the Act, and thus make little contribution to improving the practice of investigative journalism in Katsina State.